1983
DOI: 10.1210/jcem-57-5-892
|View full text |Cite
|
Sign up to set email alerts
|

Single Dose Captopril as a Diagnostic Test for Primary Aldosteronism*

Abstract: Most diagnostic tests for primary aldosteronism use maneuvers to expand the extracellular fluid volume, thereby suppressing the renin-angiotensin system. This results in a decline in plasma aldosterone concentrations in normal subjects and essential hypertension (EH) patients, but not in patients with primary aldosteronism. Captopril blocks angiotensin II synthesis and might be used as a diagnostic test for primary aldosteronism. We have measured plasma aldosterone concentrations 2 h after the administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
2

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 18 publications
1
86
0
2
Order By: Relevance
“…The ARR has been advocated as a convenient and effective method to screen for PA, with some limitations concerning a possible reduction of its accuracy by various antihypertensive drugs, posture changes, time of day, potassium levels and renal insufficiency (7)(8)(9). An elevated ARR is not diagnostic by itself and PA must be confirmed by other tests, such as a saline infusion test, fludrocortisone suppression test, captopril test and oral salt loading test, which are able to demonstrate an inappropriate autonomous ALD production (8,(10)(11)(12)(13)(14). The application of the ARR to a broader population of hypertensives has uncovered a higher prevalence of PA in both hypertensive clinic and primary care populations, with prevalence rates ranging from 3% to 32% and most patients being normokalemic (15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…The ARR has been advocated as a convenient and effective method to screen for PA, with some limitations concerning a possible reduction of its accuracy by various antihypertensive drugs, posture changes, time of day, potassium levels and renal insufficiency (7)(8)(9). An elevated ARR is not diagnostic by itself and PA must be confirmed by other tests, such as a saline infusion test, fludrocortisone suppression test, captopril test and oral salt loading test, which are able to demonstrate an inappropriate autonomous ALD production (8,(10)(11)(12)(13)(14). The application of the ARR to a broader population of hypertensives has uncovered a higher prevalence of PA in both hypertensive clinic and primary care populations, with prevalence rates ranging from 3% to 32% and most patients being normokalemic (15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Altogether the computation of the ARR, particularly when correlated to the PA value, 30 appears the most robust screening test for primary aldosteronism. 24 Now that plasma aldosterone and renin assessments are readily available in most commercial laboratories and major hospitals at a reasonable cost, measurement of these parameters in simultaneously drawn blood samples is recommended, followed by computation of the ARR (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30] The use of captopril therefore increases the utility of the ARR by increasing specificity and thus decreasing the need for confirmatory testing. In 1983, Lyons et al 30 compared the use of the ARR obtained 2 h after a dose of captopril with results obtained using the 'gold standard' saline infusion. They found that the acute suppression of aldosterone and removal of any negative feedback on circulating levels of renin using the post captopril ARR were as efficacious as the more cumbersome infusion of saline over a 4 h period.…”
Section: Captopril Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, ACEIs stimulate renin secretion by inhibiting direct negative feedback of angiotensin II in a normal person. But captopril, one of the ACEIs, was reported not to increase PRA in APA [8], and the unresponsiveness of PRA to captopril administration is there- (AP-RA) [9]. The main characteristic of this adrenal adenoma sub-type is that it resembles IHA.…”
Section: Discussionmentioning
confidence: 96%